Improving the Detection Sensitivity for Laser-Induced Breakdown Spectroscopy: A Review - Fu, Xinglan; Li, Guanglin; Dong, Daming (Frontiers in Physics, 2020)
Laser-induced breakdown spectroscopy (LIBS) is fast, on-line, causes little sample damage, and can be applied in remote field locations. In recent years, LIBS has been widely used in many fields of scientific research for element detection. Further application of LIBS is limited by the strong matrix effect, poor repeatability, and relatively weak detection sensitivity. The detection sensitivity is an important factor and needs to be improved for LIBS detection of minor or trace elements in samples. A variety of methods have been developed for this. In this invited review paper, we discusse improvements in the LIBS detection sensitivity achieved with physical enhancement methods, chemical enhancement methods, mathematical methods, and combinations of multiple methods. We discuss the enhancement mechanisms, sensitivity improvements, configurations, and effects of key factors for various methods. The advantages, disadvantages, and real-time capabilities of these methods are reviewed. Finally, new trends and future perspectives for LIBS as an efficient analytical tool are highlighted.